UV Spectrophotometric Method Development and Validation for Estimation of Trimetazidine Dihydrochloride in Bulk and Pharmaceutical Dosage Form - Rani, G. Sandhya; Phanishabareesh, L.; Shiwathmika, G.; Himad, SK. Roshan; Chinnaeswaraiah, M. (Pharmaceutical Science: New Insights and Developments Vol. 1, 2024)
The present study illustrates the development and validation of a new, simple, precise and accurate spectrophotometric method for the determination of Anti-anginal Trimetazidine dihydrochloride (TMZ) in bulk and its dosage forms using Ethanol as solvent. The drug showed its \(λ\) max at 233 nm in various concentrations. Under the optimised conditions, linear relationships with good correlation coefficients were found between the concentration ranges of 10-60 µg/ml. The precision of the method was found to be <2% of %RSD. The accuracy of the method was found in the normal ranges i.e., the recovery values were found to be in the range of 97-101%. The LOD and LOQ values of the method were found to be 0.15 and 0.45 µg/ml, respectively. The assay of the method was found in normal values of 98.87%. The proposed method is practical and valuable for its routine application in quality control laboratories for the estimation of TMZ.